Perbandingan Tingkat Kepuasan dalam Pemenuhan Kebutuhan Eksistensi Diri Remaja Kota Denpasar pada Penggunaan Media Sosial Instagram dan Tiktok - Wardani, Sandra Dewi Kusuma; Gelgel, Ni Made Ras Amanda; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium; Vol 5 No 2 (2024): Jurnal Ilmu Komunikasi Vol 5 No 2 Tahun 2024, 2024)
Instagram and Tiktok have become popular applications and are loved by teenagers in the past year. The use of these two social media platforms is sometimes overused, one of which is to show self-existence or get recognition from others. This research was conducted to determine the level of satisfaction with fulfilling the self-existence needs of Denpasar City teenagers using Instagram and Tiktok. The Papacharisi and Rubin reasons for media consumption and economic motives were applied in this research, along with uses and gratification theory and descriptive quantitative research methods. The results of this study indicate that there are differences in satisfaction in fulfilling the self-existence needs of Denpasar City teenagers using social media Instagram and Tiktok, where self-existence needs fulfillment on Instagram is satisfied, while Tiktok is not satisfied.